Ant litter fauna of forest, forest edges and adjacentgrassland in the Atlantic rain forest region of Bahia, Brazil - Majer, Jonathan; Delabie, J.; McKenzie, N. (Birkhauser Verlag, 1997)
The litter ant fauna was sampled by Winkler sacks and pitfall traps along transects running through Atlantic rain forest into an adjacent grassland. Transects ran 65 m into the forest and 45 m into the field. Ninety-seven species of ants were sampled and scored, 85 were found in the forest, 48 were found in the field and 36 were common to both habitats. There was some evidence that species richness was lowest in the field and high at the deepest point within the forest. The composition of the ant community at the different distances into the forest and field was analysed by a number of hierarchical clustering procedures and also by ordinating the data in three-dimensional space. A two-way table of the ant assemblages derived from the clustering procedure versus the groupings of transect distances obtained by the same procedure indicated that certain ant species had preferences for the field or particular distances into the forest. It is concluded that although the ant fauna of Atlantic rain forest is severely affected by clearing, a forest-like ant fauna is able to persist right up to the interior edge of the forest.